Organizational Culture and Ethics in Decision-Making - Anak Manggai, Bibiana; bin Thukiman, Kassim; Fauzi bin Othman, Muhammad; Khairi bin Abdul Majid, Muhammad (International Journal of Engineering and Technology, 2018)
Malaysia was recorded outnumber of accidents in the world. The traffic Police is the responsible body forÂ ensuring to maintain the law on the road which assists the public for smooth travelling The media reports stated that the traffic police uses their power in wrong ways and is showing not profession with their duties. This happens due to lack of organizational culture among civil servants which are not practiced in the right ways according to the justice and their professions.Â Therefore, this article focuses on the organizational culture that should be practiced and the decisions that need to be practiced. Further, the ethical factors based decisions should be performed by traffic police. The topic selected will expect to improve the organizational culture and an ethical decision making among lawâ€™s practitioner and traffic police. In addition, the positive view can also give to the public on the ethical decision making that could be practiced by traffic police. In conclusion, the improvement of organizational culture should be refined to produce law practitioners and implementers in ethical especially for civil servants in decision-making.Â Â